Analysis of the physical properties and photoelectrochemical behavior of c-Si/a-SiC:H(p) photocathodes for solar water splitting - Mejia Chueca, María del Carmen (2022)
Photoelectrochemical (PEC) processes have become an efficient and viable method for solar energy conversion into zero-emission fuels by harnessing and storage the power of the sun, which offers an environment-friendly approach. Hydrogen is considered as a sustainable and suitable energy alternative in comparison to energy systems based on the consumption of conventional hydrocarbon fuels. In particular, hydrogen production by PEC water splitting represents an attractive alternative to enhance the efficiency of water splitting process using sun light. Current research in this field is devoted to the fabrication and evaluation of new photoactive materials that upon sunlight absorption enable water-splitting PEC reactions with high efficiency and durability. Silicon based compounds offer a good opportunity as photoactive material due to its high abundance and current scalable technologies. Silicon is the eighth most abundant element in the universe and constitutes up to 27.2% of the earth’s crust weight [1]. Particularly, hydrogenated amorphous silicon carbide (a-SiC:H) thin films have been tested as photocathode material for photo-assisted electrolysis, exhibiting solar to hydrogen conversion efficiencies up to 7.5 %. Due to the capability to tailor the bandgap (1.8 - 3.3 eV) by the incorporation of carbon in a-Si:H, this material has turned out to be a promising candidate for PEC cells, fulfilling the optical bandgap (Egap) primary requirement, i.e. Egap > 2.2 eV. Additionally, the carbon incorporation leads to an enhancement of the corrosion resistance properties in aqueous media. It has been theoretically estimated that a PEC device with an a-Si0.9C0.1:H absorption layer exhibiting 2.0 eV of energy bandgap, can generate a photocurrent density Jph of 15 mA/cm2 (solar-to-hydrogen conversion efficiency ∼18 %) when submitted to an Air mass (AM) 1.5 solar spectrum [2]. The specific value of 1.5 for the Air mass is selected for standardization purposes, based on the analysis of solar irradiance data in the United States, and corresponds to a power of 1000 W/cm2 [3]. In the present work, a similar material a-Si0.5C0.5:H exhibiting 2.76 eV of energy bandgap generates a Jph of 17 mA/cm2 when submitted to the same light spectrum. This reflects an improvement in the use of a-SiC:H in PEC water splitting. Research on single thin film photoactive materials does not typically consider the role of the silicon substrate in the photoelectrochemical performance. In this sense, the photoelectrode is a system formed by a p-p, n-n or n-p structure, which depending on the depth of the space charge region may have an important impact on the photoelectrode performance. In this work, this substrate effect has been considered and studied. PEC performance of a-SiC:H is often limited by its non-ideal energy band-edge alignment to the H2O/O2 redox potential, thus limiting the oxygen evolution reaction (OER) and the whole water splitting process [4]. To overcome this downside, an external bias needs to be applied, contributing to counteract the overpotential required to trigger the direct water splitting reaction. The external bias also contributes to reduce overpotentials due to the presence of a surface SiO2 barrier layer and compensates interface charge carriers recombination as well. Previous studies have demonstrated that by removing the SiO2 native layer vii from a-SiC:H(i) surface, Jph values over 6 mA/cm2 can be achieved at a potential of -1.4 V vs. Ag/AgCl in contrast to values lower than < 4 mA/cm2 obtained without the oxide removal. In fact, the existence of surface states (SS) originated from the hydroxyl group termination on the oxide surface, form an electronic state that is typically located within the semiconductor bandgap. The theory that such states act as recombination centers for minority photo carriers, fits quite well with the assumption that surface recombination competes with charge transfer from the semiconductor band towards the electrolyte. Additionally, it has been reported that depending on the density and energetic position of SS, these can provide another favorable pathway for indirect charge transfer to the solution, competing with the undesirable recombination mechanism. Knowledge in this field is limitated to full-drift diffusion simulations in steady-state and dynamic regimes for photo-anodic currents in crystalline materials. In the current work, an experimental study has been carried out over an amorphous material (a-SiC:H) acting as photocathode for PEC water splitting. Thus, adding knowledge in this field. Attempts to understand the role of a-SiC defects in PEC water splitting performance have been carried out in 2009 by Simonds et al. [5]. As a result of these, defects density in the bulk of the a-SiC increases with carbon concentration, from ∼9 × 1016 cm−3 (6%C) to ∼8 × 1017 cm−3 (11%C), leading to a reduction of the PEC performance. On the other hand, defect densities in the SiC/SiO2 interface (SS) were approximated by Gaussian distributions with maximums of ∼2 × 1012 cm−2 · eV−1 (Ivanov et al. [6]). The latter finding was retrieved from Capacitance-Voltage (C−V) measurements over metal-oxide-semiconductor (MOS) structures, and fit quite well with the SiC SS density distributions reported in this work. The current work consists in three parts. In the first part, Bandgap engineering of a-SiC:H thin films was carried out to assess the material light absorption without compromising its photoelectrochemical water splitting capabilities. The tailoring was performed by varying the hydrogen concentration in the semiconductor and by post-deposition isochronical annealing treatments from 200 to 700 ◦C. By isochronical annealing, the same sample is submitted to the different temperature steps, from low to high temperature. After this analysis, the most suitable samples for water splitting application were evaluated as photocathodes in 1 M sulfuric acid under chopped light illumination. These a-SiC:H samples were doped with aluminum and deposited on different Silicon substrate conductivity types to assess the substrate influence in the a-SiC:H(Al) photocurrent response. This constitutes the second part or the work. Finally, in the third part, the role of SS in the photocathodic current for a-SiC:H(Al) absorber layers was experimentally analyzed. This analysis was based on steady-state and dynamic electrochemical models. Results concerning a-SiC:H(Al) photocathode stability under darkness and illumination conditions are also shown and discussed in this part. Concerning the findings and the novelty in this work, localized a-SiC:H(Al)/SiO2 SS would take part in a desirable mechanism of indirect electron charge transfer viii to the electrolyte, and thus, conduct hydrogen evolution reaction. Related to the SiO2 native layer, the evidence suggests that the SiO2 layer reduction during PEC tests triggers a favorable semiconductor-electrolyte interface. This interface exhibits less overpotential barriers which promotes photocurrent generation. A correlation exists between the retrieved SS density (NSS) and Urbach energy (EU) values. The EU is associated with disorder-induced electronic tail states or Urbach tails, which are localized states near the semiconductor band-edges. This correlation, as well as other a-SiC:H(Al)/SiO2 interface studies, support the reliability of our NSS calculations for the c-Si(p)/a-SiC:H(Al)/SiO2/electrolyte system. Finally, a charge transfer mechanism assisted by photogenerated minority carriers from the c-Si substrate has been also proposed in this work